IN VITRO SCREENING OF LACTIC ACID BACTERIA AS BIOCONTROL AGENTS FOR BIOPRESERVATION OF PERISHABLE AGRO-FOOD PRODUCTS - Florentina BADEA; Mircea Cosmin PRISTAVU; Constantin Alexandru ALDEA; Florentina ISRAEL-ROMING; Florentina MATEI (Scientific Papers. Series D. Animal Science, 2024)
The aim of this study was to evaluate in vitro the potential of different strains of lactic acid bacteria (LAB), belonging to Enterococcus faecium, Lactobacillus brevis, Lactobacillus farciminis, Lactobacillus fermentum, Lactobacillus plantarum, Pediococcus acidilactici, Pediococcus pentosaceus and Weissella cibaria, for their potential use for increasing the shelf life of different perishable food products. Several screening tests were taken into account, mainly related to their probiotic potential, but also the potential use as biocontrol agents during storage. The strains of P. pentosaceus, L. fermentum, and L. plantarum had the greatest biopreservation potential, with a spectrum of antimicrobial activity against a wide range of pathogenic bacteria and food spoilage fungi. They are capable of producing bacteriocins, exopolysaccharides, organic acids (lactic and acetic acids), enzymes (protease and phytase). In addition, freeze-drying with glucose as a cryoprotective agent resulted in a high survival rate of LAB strains, with a survival rate exceeding 50%. The aforementioned findings suggest that out of the LAB strains tested, L. plantarum MI207 represents a viable option for extending the shelf life of fresh, minimally processed food products in a sustainable manner.
Keywords: lactic acid bacteria; preservation; perishable food; probiotic.